Status quo bias impedes active travel policy by changing the process of opinion formation - Ylva Andersson; Féidhlim McGowan; Shane Timmons; Pete Lunn (The Economic and Social Research Institute (ESRI), 2023)
This study demonstrates how status quo bias (SQB) acts as an obstacle to active travel policy. A pre-registered experiment was undertaken to measure the strength of SQB and to illuminate its likely causes. A large, nationally representative sample evaluated descriptions of a town layout designed to promote cycling and walking ahead of driving. Participants were randomised such that the (otherwise identical) layout was either planned or already in place. Those in the 'planned' condition gave lower evaluations, demonstrating strong SQB. The estimated effect size was stronger than the influence of being a cyclist or regular driver. SQB was unrelated to psychological scales measuring general resistance to change and loss aversion. Participants in the 'planned' condition also sought out different information about the town layout, immediately focussing on potential downsides - a behaviour consistent with some psychological theories of evaluation. The findings have implications for active travel policy and other pro-climate policies that require societal acceptance of change.
Keywords: 330; active travel; cycling; Status Quo Bias; public opposition; climate policy